Examining Effectiveness and Predictors of Treatment Response of Pivotal Response Treatment in Autism: An Umbrella Review and a Meta-Analysis - Uljarević, Mirko; Billingham, Wesley; Cooper, Matthew N.; Condron, Patrick; Hardan, Antonio Y. (Frontiers in Psychiatry, 2022)
The current study aimed to provide a comprehensive appraisal of the current evidence on the effectiveness of Pivotal Response Training (PRT) for individuals with autism spectrum disorder (ASD) and to explore predictors of treatment response. We conducted a systematic review of the following electronic databases and registers: PsycINFO, Medline, Embase, Cochrane Central Register of Controlled Trials, ERIC, Linguistics and Language Behavior Abstracts. Six systematic reviews were identified, two with meta-analytic component. Identified reviews varied widely in terms of their aims, outcomes, and designs which precluded a unified and consistent set of conclusions and recommendations. Ten RCTs were identified. Eight of identified RCTs reported at least one language and communication-related outcome. Statistically significant effects of PRT were identified across a majority of identified RCTs for a range of language and communication skills. However, evidence for positive treatment effects of PRT on outcome measures assessing other domains was less robust and or specific. Overall, both previous systematic reviews and new meta-analysis of the RCTs suggest that PRT shows promise for improving language and communication. Only four RCTs examined the association between baseline child characteristics and treatment outcomes, however, no consistent pattern emerged. This review has identified several key methodological and design improvements that are needed to enable our field to fully capitalize on the potential of RCT designs and characterize detailed profiles of treatment responders. These findings are essential for informing the development of evidence-based guidelines for clinicians on what works for whom and why.